2011
DOI: 10.1111/j.1467-9396.2010.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign News and Spillovers in Emerging European Stock Markets

Abstract: We analyze foreign news and spillovers in the emerging EU stock markets (the Czech Republic, Hungary, and Poland). We employ high‐frequency five‐minute intraday data on stock market index returns and four classes of EU and US macroeconomic announcements during 2004–07. We account for the difference of each announcement from its market expectation and we jointly model the volatility of the returns accounting for intraday movements and day‐of‐the‐week effects. Our findings show that intraday interactions on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 40 publications
5
27
0
Order By: Relevance
“…Also, it concludes that all variables are co-integrated with LSMI t in the long-run and any deviations may occur in the short-run. The results are confirmed with others results studies (Chaudhuri and Smiles, 2004;Hanousek and Kocenda, 2011;Ibrahim and Aziz, 2003).…”
Section: Bounds F-statistics Testsupporting
confidence: 83%
See 2 more Smart Citations
“…Also, it concludes that all variables are co-integrated with LSMI t in the long-run and any deviations may occur in the short-run. The results are confirmed with others results studies (Chaudhuri and Smiles, 2004;Hanousek and Kocenda, 2011;Ibrahim and Aziz, 2003).…”
Section: Bounds F-statistics Testsupporting
confidence: 83%
“…At the same time, numerous studies analyzed the relationships between macroeconomic variables and stock market indices using GARCH volatility time-series models (Bhar and Malliaris, 2011;Chen, 2009;Erdem et al, 2005;Hanousek and Kocenda, 2011;Hsing, 2011;Hsing and Hsieh, 2012;Kim et al, 2004;Nguyen, 2011;Rangel, 2011). Also, the results indicated that the conditional volatility of macroeconomic variables significantly influence stock market indices.…”
Section: Review Of Previous Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanousek and Kočenda, 2011). For that reason, we define possible impact on the stock markets of CIVETS as hypothetical effects of macroeconomic news surprises.…”
Section: Description Of the Datamentioning
confidence: 99%
“…In this survey a group of economists reveal their expectations about future macroeconomic indicator values. As the expectations are often not in the form of stock market index value, but in the units of the respective macroeconomic indicators, the news surprises are calculated and standardized to facilitate interpretation by using the following approach (for similar way of surprise calculation see Balduzzi et al, 2001, andKočenda, 2011):…”
Section: Description Of the Datamentioning
confidence: 99%